Educational Traditions of the Prophet’s Sports in the Formation of Physical and Mental Health: Hadis tentang Pendidikan Olahraga Nabi dalam Pembentukan Kesehatan Fisik dan Jiwa - Giyarsi, Giyarsi; Idi Warsah; Toha Andiko (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2024)
Modern society's awareness of the importance of a healthy lifestyle has brought new ideas not only limited to diet and sleep but also exercise. In this case, exercise is believed to be important in realizing physical and mental health. However, some groups limit the practice of exercise to archery, swimming, and horseback riding, as referred to the hadith delivered by the prophet. This study aims to analyze the concept of sports in the Prophetic traditions as a basis for developing a holistic sports education program, as well as to examine the permissibility of the Prophetic sports tradition through the contextualization of hadith in the modern era. Through a qualitative approach based on literature study, the author uses a collection of literature and relevant sources of information as research sources. In analyzing the data, the author uses the stages proposed by Miles & Huberman, namely data identification, data reduction, data presentation, and conclusion drawing. From two questions; how is the contextualization of sports hadith in realizing physical and mental health, and how is the application of hadith about sports in the development of sports education programs, the results show that the concept of sports in the prophet's traditions is not seen from the form of sports alone, such as swimming, archery and horse riding, but rather on the aspect of its purpose and usefulness. Philosophically, the purpose and benefits of sports education in children through the context of archery and horse riding during the Prophet's time are more directed at the form of children's education so that they become individuals who understand the goals and objectives of life, calmness, concentration, and strategies in achieving these goals, including mastery of modern technological means that support the ease of physical activity in facilitating towards every goal of life.